Application Value of Emergency Bedside Echocardiography in Early Warning of Acute and Severe Shock and Clinical Classification. (19th July 2022) - Ye, Juan; Lin, Yan; Chen, Shaolin
Abstract : Objective . A case-control study was conducted to explore the application value of emergency bedside echocardiography in early warning of acute and severe shock and clinical classification. Methods . A total of 135 critically ill patients admitted to ICU from August 2019 to November 2020 were divided into shock group (n = 53 ) and nonshock group (n = 82 ) according to the occurrence of shock. The internal diameter index of inferior vena cava was measured and recorded by bedside ultrasound in patients with shock before and after treatment and in patients without shock. Shock index and inferior vena cava diameter deformation index (SCI) were calculated according to the results. The diagnostic time and curative effect of different ultrasonic examination methods for the types of shock were compared and analyzed. Results . At admission, the maximum and minimum ventilation of inferior vena cava in patients without shock were higher than those in the shock group, and the internal diameter deformation index of inferior vena cava in the shock group was higher than that in the shock group (P < 0.05 ). In the shock group, IVCmax and IVCmin before and after treatment were higher than those before resuscitation, while SCI was lower than that before resuscitation. The results of ROC curve analysis showed that SCI and IVCmin were significantly better than IVCmax and IVCmin in predicting shock area and slightly better than IVCmin. There was significant difference in diagnosis time between the two groups (P < 0.05 ). The specificity, positive predictive value, and negative predictive value of emergency ultrasound diagnosis were lower than those of clinical diagnosis (P < 0.05 ). The sensitivity, specificity, positive predictive value, and negative predictive value of emergency ultrasound diagnosis were lower than those of clinical diagnosis (P < 0.05 ). The sensitivity and positive predictive value of the emergency ultrasound group were higher than those of the routine ultrasound group (P < 0.05 ). The diagnosis rate of shock type AUC in the emergency ultrasound group was 0.854, and the diagnostic value was high. Conclusion . IVCmax, IVCmin, and SCI obtained by bedside ultrasound have certain clinical significance for the diagnosis and treatment of shock. Emergency bedside ultrasound examination and measurement of shock patients are helpful to quickly evaluate and identify the types of early shock.